Sustainable development in European Union as expression of social, human, economic, technological and environmental progress - Maria-Daniela Tudorache (Theoretical and Applied Economics, 2020)
This paper analyse the way how the sustainable developments components are interacting between them and reflects on a possible trade-off between social, human, economic, technological and environmental progress. In this context, I have computed the Pearson correlation coefficient between the mentioned forms of development for 2010-2018 period, but in some cases, my analysis was limited to a lower period due to the data availability. At all, I have concluded that social, human, economic, technological and environmental development are positively linked, but the link between technological and social development depends on the degree of automation which may spread certain social imbalances across the European Union on short-run. However, the link between social and technological development remain positive when it is assessed through the digitalisation channel or the growth of the IT&C sector.
Keywords: O10; B55; A10; O14; O13; O15; 330; development; social; economic; technology; environment; human; sustainable